Partial restoration of cardiovascular function by embryonic neural stem cell grafts after complete spinal cord transection - Hou, Shaoping; Tom, Veronica J.; Graham, Lori; Lu, Paul; Blesch, Armin (The journal of neuroscience, 2013)
High-level spinal cord injury can lead to cardiovascular dysfunction, including disordered hemodynamics at rest and autonomic dysreflexia during noxious stimulation. To restore supraspinal control of sympathetic preganglionic neurons (SPNs), we grafted embryonic brainstem-derived neural stem cells (BS-NSCs) or spinal cord-derived neural stem cells (SC-NSCs) expressing green fluorescent protein into the T4 complete transection site of adult rats. Animals with injury alone served as controls. Implanting of BS-NSCs but not SC-NSCs resulted in recovery of basal cardiovascular parameters, whereas both cell grafts alleviated autonomic dysreflexia. Subsequent spinal cord retransection above the graft abolished the recovery of basal hemodynamics and reflexic response. BS-NSC graft-derived catecholaminergic and serotonergic neurons showed remarkable long-distance axon growth and topographical innervation of caudal SPNs. Anterograde tracing indicated growth of medullar axons into stem cell grafts and formation of synapses. Thus, grafted embryonic brainstem-derived neurons can act as functional relays to restore supraspinal regulation of denervated SPNs, thereby contributing to cardiovascular functional improvement.
Gesehen am 29.10.2021